Learning Cocoa (O'Reilly, 2001)
Cocoau2122 is one of the principal application environments for Mac® OS X. Among Cocoa's many attributes, its advanced object-oriented APIs allow you to develop in both Java and Objective-C. This revolutionary new way of developing sophisticated applications for the Macintosh is both powerful and easy. With Learning Cocoa you'll become familiar with Cocoa application development, using Objective C, not merely by reading, but by doing. The book begins with a discussion of essential object-oriented programming concepts for those with no previous experience. It proceeds through an introduction to the Cocoa environment, development, tools, and some simple tutorials to help you become familiar with the basic elements of Cocoa programming. The remaining tutorials guide you as you create a series of increasingly complex example applications. The techniques and concepts you learn in one tutorial lay the foundation for the more advanced techniques and concepts in the next. You don't need extensive programming experience to complete the examples in this book, though it would be helpful to have some experience with the C programming language. The code for each example is included in the text so you can simply type it in. If you're already familiar with an object-oriented programming language like Java or Smalltalk, you'll quickly feel right at home with Objective-C, the language used throughout this book. As you ease your way into the experience of Cocoa programming, you're encouraged to play, to explore, to "kick the tires." You'll finish this book much better prepared to take on serious application development with Cocoa, and you'll find Apple's development environment not only less mysterious, but one that you'll be eager to program inches Written by insiders at Apple Computer, the book brings you information that you can't get anywhere else--and a potential leg up in the Mac OS X application development market.